Hypothetical performance of syndrome-based management of acute paediatric admissions of children aged more than 60 days in a Kenyan district hospital. - English, M; Berkley, J; Mwangi, I; Mohammed, S; Ahmed, M; Osier, F; Muturi, N; Ogutu, B; Marsh, K; Newton, C (2003)
OBJECTIVE: To investigate whether the outpatient, syndrome-based approach of the Integrated Management of Childhood Illness (IMCI) protocol could be extended to the inpatient arena to give clear and simple minimum standards of care for poorly resourced facilities. METHODS: A prospective, one-year admission cohort retrospectively compared hypothetical performance of syndrome-based management with paediatrician-defined final diagnosis. Admission syndrome definitions were based on local adaptations to the IMCI protocol that encompassed 20 clinical features, measurement of oxygen saturation, and malaria microscopy. FINDINGS: After 315 children with clinically obvious diagnoses (e.g. sickle cell disease and burns) were excluded, 3705 admission episodes were studied. Of these, 2334 (63%) met criteria for at least one severe syndrome (mortality 8% vs <1% for "non-severe" cases), and half of these had features of two or more severe syndromes. No cases of measles were seen. Syndrome-based treatment would have been appropriate (sensitivity >95%) for severe pneumonia, severe malaria, and diarrhoea with severe dehydration, and probably for severe malnutrition (sensitivity 71%). Syndrome-directed treatment suggested the use of broad-spectrum antibiotics in 75/133 (56% sensitivity) children with bacteraemic and 63/71 (89% sensitivity) children with meningitis. CONCLUSIONS: Twenty clinical features, oxygen saturation measurements, and results of malaria blood slides could be used for inpatient, syndrome-based management of acute paediatric admissions. The addition of microscopy of the cerebrospinal fluid and haemoglobin measurements would improve syndrome-directed treatment considerably. This approach might rationalize admission policy and standardize inpatient paediatric care in resource-poor countries, although the clinical detection of bacteraemia remains a problem.